Synthesis of water-dispersible silicon-containing hydroxyapatite nanoparticles with adjustable degradation rates and their applications as pH-responsive drug carriers. Issue 115 (13th December 2016) - Lin, Kaili; Zhang, Na; Yin, Zhilan; Shen, Yuhui; Zhang, Weibin
Abstract : An environmentally friendly method was developed to synthesize water-dispersible Si-HAp nanoparticles with adjustable degradation rates, high loading capacities for anticancer drugs, and sustained and pH-dependent drug release properties. Abstract : Silicon-containing hydroxyapatite (Si-HAp) nanoparticles with adjustable degradation rates were successfully synthesized via simple hydrothermal treatment of a precursor, calcium silicate hydrate powder, in trisodium phosphate aqueous solution. The degradation rate of the products could be facilely tailored by regulating the hydrothermal temperature, while the obtained Si-HAp nanoparticles exhibited high loading capacities toward doxorubicin (DOX) as well as sustained and pH-dependent drug release properties. HeLa cell culture results confirmed that the toxicity of DOX loaded in Si-HAp nanoparticles was more sustained than that of free DOX. Their biodegradability, good water dispersibility and drug-loading capacity, and sustained and pH-responsive drug release properties suggest that these synthetic Si-HAp nanoparticles have great potential applications as drug carriers.